Evaluation of Traffic Impact of Tourism Attraction Development Gajah Mungkur Reservoir, Wonogiri Regency - Amal, Mohammad Fatkhul; Sunarjono, Sri; Rum Harnaeni, Senja (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
The Gajah Mungkur Reservoir is one of the popular destinations by the people of Wonogiri. The Regional Government of Wonogiri Regency plans to develop the Gajah Mungkur Reservoir in 2024. The development plan for the Gajah Mungkur Reservoir is predicted to have the potential to have potential impact on decreasing the performance of the road network and intersections in the surrounding area, so a study is needed regarding the current performance of parking, road networks and intersections, current generation and attraction, parking performance, road and intersection networks after development and handling traffic impacts due to development. The analysis method uses MKJI 1997. Based on the results of the analysis, it can be seen that the performance of Jalan Wonogiri - Manyaran - Blimbing/Bts. Provinsi DIY (B-T) in the 2023 Existing condition has a saturation degree of DS=0.43 with a service level of "B", while for Jalan Wonogiri - Manyaran - Blimbing/Bts. Prov. DIY (T-B), degree of saturation DS=0.39 with service level "B". The performance of Simpang 4 Pintu Masuk on the 2023 Existing has a degree of saturation DS=0.407; Queue Opportunity is 19.14% and the intersection delay is 7.89 seconds/pcu with a service level of "B". Performance of Simpang 4 Pintu Keluar in 2023 Existing has a degree of saturation DS=0.450; the Queue Opportunity is 21.59% and the intersection delay is 8.40 seconds/pcu with a service level of "B". In the existing conditions in 2023, the attraction of the Gajah Mungkur Reservoir is 155.38 pcu/hour and the generation is 116.88 pcu/hour. In 2024 construction period until 2027 after development, the performance of Jalan Wonogiri - Manyaran - Blimbing/Bts. Provinsi DIY is still in good condition with a service level of "C". However, in 2028 after development, the performance of the Jalan Wonogiri - Manyaran - Blimbing/Bts. Provinsi DIY has a decrease in performance and an increase in the DS value where the performance of the Jalan Wonogiri - Manyaran - Blimbing/Bts. Provinsi DIY (B-T) has DS = 0.76 with a service level of "D" while for Jalan Wonogiri-Manyaran-Blimbing/Bts. Prov. DIY (T-B) has DS = 0.60 with a service level of "C". The performance of Simpang 4 Pintu Masuk in 2028 with development has a degree of saturation DS=0.583; the chance of queuing is 30.58% and the intersection delay is 9.76 seconds/pcu with a service level of "B". The performance of Simpang 4 Pintu Keluar in 2028 with development has a degree of saturation DS=0.643; Queue Opportunity is 35.53% and the intersection delay is 10.44 seconds/pcu with a service level of "B". Parking performance, both existing and after development, is still able to accommodate all vehicles entering the Gajah Mungkur Reservoir. Recommendations for handling traffic impacts (Do Something) due to the Gajah Mungkur Reservoir Development consist of 2 alternatives, namely alternative 1 by reducing side obstacles by controlling street vendors on the road shoulder and prohibiting on-street parking while alternative 2 is by arranging separation of traffic directions on the Jalan Wonogiri - Manyaran - Blimbing/Bts. Prov. DIY. Of the two treatment alternatives, alternative 1 provides better results than alternative 2. Performance of the Jalan Wonogiri - Manyaran - Blimbing/Bts. Provinsi DIY experienced a decrease in the DS value for each direction from the previous DS=0.76 with a service level of "D" for the B-T direction to DS=0.74 with a service level of "C" while for the T-B direction from the previous DS=0.60 with service level "C" becomes DS=0.59 with the same service level, namely "C". The performance of Simpang 4 Pintu Masuk in the 2028 with Development & Do Something 1 shows good results, with a degree of saturation of 0.576; Queue Opportunity is 30.11% and the intersection delay is 9.69 seconds/pcu with a service level of "B". The performance of Simpang 4 Pintu Keluar in 2028 with Development & Do Something 1 shows good results, with a degree of saturation of 0.637; the Queue Opportunity is 34.95% and the intersection delay is 10.37 seconds/pcu with a service level of "B". Apart from that, it is also recommended to put several road equipment both inside and outside the Gajah Mungkur Reservoir location.